Courtyards houses of Kolkata: bioclimatic, typological and socio-cultural study - Das, Nibedita (Kansas State University, 2006)
This research explores the bioclimatic and socio-cultural benefits of Kolkata’s courtyard houses. A typological and historical analysis of courtyard houses from around the world, as well as in Kolkata, provides a context for the field research. The main intention of this study is to explore the roles of solar shading and natural ventilation in courtyard houses located in the hot-humid climatic region. For this purpose interviews with the heads of household of ten courtyard houses in Kolkata were conducted in January 2005, to finally choose three houses for detailed experimental analysis. All three houses have high thermal construction and similar socio-economic conditions. This helped in comparing the results of the temperature (both ambient and surface temperatures) and air speed measurements among the three houses referred to as House A, House B and House C houses. House A and House C houses have shallow courtyards (high aspect ratios which in both cases equal 0.95), while House B house has a deep courtyard (low aspect ratio equal to 0.21). Further, ventilation analysis has been done with the help of Computational Fluid Dynamics (CFD) software. The simulation study and the experimental data measurements focused on the comfort conditions generated within the house based on their differences in proportion of form and massing. The effects of solar shading and natural ventilation on activity patterns and uses of a space are also examined through occupant surveys. Finally, this research explores the historic courtyard houses in Kolkata, with a view to address the benefits of the universal courtyard form of design and speculate the appropriateness of the vernacular courtyard form in the modern architectural arena of Kolkata.
Keywords: courtyards; bioclimatic; kolkata; socio-cultural; Architecture (0729)